2021
DOI: 10.55453/rjmm.2021.124.4.1
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the complications of acute and chronic mercury exposures. Past, present and future

Abstract: Mercury is a chemical element that has been known since prehistoric times and has been used over time as a component of paints, in the treatment of various diseases, and later in various industrial compounds. Mercury enters the body transcutaneously, by inhaling or by ingesting food contaminated with mercury. The most common cause of mercury poisoning is eating seafood, but people can get mercury poisoning from industrial processing, thermometers, dental work, and old paints. The most vulnerable are people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hg 0 (metallic), Hg 2 2+ (mercurous), and Hg 2+ (mercuric) mercury are the three states of inorganic mercury. Mercury’s pharmacokinetics and biotransformation are determined by its chemical and physical state …”
Section: Types Structure and Sources Of Mercury And Pharmacokinetic P...mentioning
confidence: 99%
See 4 more Smart Citations
“…Hg 0 (metallic), Hg 2 2+ (mercurous), and Hg 2+ (mercuric) mercury are the three states of inorganic mercury. Mercury’s pharmacokinetics and biotransformation are determined by its chemical and physical state …”
Section: Types Structure and Sources Of Mercury And Pharmacokinetic P...mentioning
confidence: 99%
“…These instances are potentiated to promote unexpected and nongenetical cancers. It has been reported that Hg 2+ with thiol-compounds can form mercaptans and reduce the thiol-based antioxidants in cells, which is considered a potential step to induce cancer . A case study in Poland revealed the occurrence of leukemia among a group of farmers who used mercury-containing fungicides in their farmlands .…”
Section: Mercury Toxicity On Human Health: Effects and Molecular Mech...mentioning
confidence: 99%
See 3 more Smart Citations